A missing cornerstone in the Norwegian Priority Commission's weighting scheme - Sub-treatment balancedness is a necessary property for priority setting criteria - Mathias Barra; Kim Rand-Hendriksen (University of Oslo, 2016)
The Norwegian government recently put in place a priority commission tasked with suggesting a set of explicit criteria for priority setting in the health care sector. The commission suggested three criteria, the first two of which equate to cost-effectiveness, where, essentially, the gain is measured in terms of Quality Adjusted Life Years (QALYs). The third criteria specifies that the number of QALYs be multiplied by a factor depending on the total health loss - also measured in QALYs - without the treatment in question. In this paper, we will show that the suggested weighting scheme creates contradictory situations in which the priority of treatment programmes will change based on arbitrary bundling (where two or more treatments are combined into one) or sub-divisions (where a treatment is split up into two or more components.) We show that these types of problems can be avoided or ameliorated if the QALY weighting scheme satisfies a property which we call sub-treatment balanced - informally, that the total weighted QALY gain is preserved when treatments are bundled or sub-divided. To our best knowledge, this property has not previously been discussed in the priority setting literature. We demonstrate that sub-treatment balance can easily be achieved in general, and in particular we show how to adapt the weighting scheme suggested by the Norwegian priority commission in order to satisfy this sub-treatment balance. Finally, we argue that any weighting scheme used in health care priority setting should be sub-treatment balanced with respect to any other attribute of a treatment which policy makers would want to take into account when making their decisions. At the time of writing, the Norwegian government has yet to conclude on a final set of criteria for prioritization, and a task-group, lead by professor Jon Magnussen, is re-evaluating the severity criterion suggested by the priority commission. However, sub-treatment balance is still relevant, as it should be required of any weighing scheme, and is crucial given that (i) the criterion results in weighting QALYs, and (ii) if the selected measure of severity is affected by the administered treatment.   Published: Online November 2015. In print August 2016.